The taxonomic value of the structures for the insertion of the stylet muscles in the Eutardigrada, and description of a new genus - Pilato, Giovanni (Zootaxa, 2013)
The new genus Dastychius has been instituted for the species Isohypsibius improvisus Dastych, 1984. It has claws of the Isohypsibius type, rigid buccal tube without ventral lamina and with ridge-shaped apophyses for the insertion of the stylet muscles; peribuccal lamellae absent; peribuccal papulae seem to be present but the datum should be confirmed; pharyngeal bulb with apophyses and placoids, lunules present in the known species; smooth eggs laid in the exuvium. The apophyses for the insertion of the stylet muscles have some peculiarities that justify the institution of a new genus. They are long, uninterrupted ridges tailing off caudally almost reaching the stylet supports; at almost a quarter of their length they have an incision and a septum never noted in other genera of Eutardigrada. In the author’s opinion it is possible to hypothesize that all the structures for the insertion of the stylet muscles recognizable in the Eutardigrada may be derived from long ridge-shaped apophyses (but without incision and septum). The comparison of the shape of the apophyses for the insertion of the stylet muscles in the Eutardigrada seems to indicate that this character has taxonomic value at level of genus but not at family level.